Comparison of 2-Chloroprocaine, Bupivacaine, and Lidocaine for Spinal Anesthesia in Patients Undergoing Knee Arthroscopy in an Outpatient Setting: A Double-Blind Randomized Controlled Trial. Issue 5 (September 2016) - Teunkens, An; Vermeulen, Kristien; Van Gerven, Elke; Fieuws, Steffen; Van de Velde, Marc; Rex, Steffen
Abstract : Background and Objectives: Knee arthroscopy is a well-established procedure in day-case surgery, which is frequently performed under spinal anesthesia. It is, however, controversial whether the choice for a specific local anesthetic translates into relevant outcomes. We hypothesized that the use of 2-chloroprocaine would be associated with a faster recovery from sensorimotor block. Methods: Ninety-nine patients were included in this prospective, double-blind, randomized controlled trial and randomly allocated to receive either 40 mg 2-chloroprocaine, 40 mg lidocaine, or 7.5 mg bupivacaine. The primary endpoint was the time until complete recovery of sensory block. Secondary endpoints included time to recovery from motor block, failure rates, incidence of hypotension/bradycardia, postoperative pain, first mobilization, voiding and discharge times, and the incidence of transient neurologic symptoms. This clinical trial was registered prior to patient enrollment (EudraCT 2011-003675-11). Results: Patients in the chloroprocaine group had a significantly shorter time until recovery from sensory block (median, 2.6 hours; interquartile range [IQR], 2.2–2.9 hours) than patients in the lidocaine group (3.1 hours; IQR, 2.7–3.6 hours; P < 0.006) and in the bupivacaine group (6.1 hours; IQR, 5.5 hours to undefined hours; P < 0.0001). Chloroprocaine was associated with a significantly faster recovery from motor block than lidocaine and bupivacaine. Times to first mobilization, voiding, and discharge were significantly shorter for chloroprocaine when compared with bupivacaine, but not with lidocaine. In the bupivacaine group, patients needed significantly less rescue medication for postoperative pain when compared with lidocaine and chloroprocaine. Groups did not differ with respect to patient satisfaction, incidence of bradycardia/hypotension, and transient neurologic symptom rate. Conclusions: For spinal anesthesia in patients undergoing ambulatory knee arthroscopy, chloroprocaine has the shortest time to complete recovery of sensory and motor block compared with bupivacaine and lidocaine.